Visual Experience Is Necessary for the Development of Multisensory Integration - Wallace, Mark T. (J Neurosci, 2004)
Multisensory neurons and their ability to integrate multisensory cues develop gradually in the midbrain [i.e., superior colliculus (SC)]. To examine the possibility that early sensory experiences might play a critical role in these maturational processes, animals were raised in the absence of visual cues. As adults, the SC of these animals were found to contain many multisensory neurons, the large majority of which were visually responsive. Although these neurons responded robustly to each of their cross-modal inputs when presented individually, they were incapable of synthesizing this information. These observations suggest that visual experiences are critical for the SC to develop the ability to integrate multisensory information and lead to the prediction that, in the absence of such experience, animals will be compromised in their sensitivity to cross-modal events.